One Cycle of Concurrent Chemotherapy vs. Two Cycles of Concurrent Chemotherapy With Radiation Therapy in Patients With Limited-Stage Small Cell Lung Cancer - Yu, Hao; Zhang, Jiaqi; Zhang, Zhen; Wang, Youyou; Xu, Guangying; Xu, Liming; Liu, Ningbo; Zhao, Lujun; Wang, Ping (Frontiers in Oncology, 2022)
Background: The optimal number of concurrent chemotherapy cycles during thoracic radiotherapy (RT) in patients with limited stage-small cell lung cancer (LS-SCLC) is not well defined. The purpose of this study was to evaluate the impact of the number of concurrent chemotherapy cycles on prognosis of LS-SCLC. Material and Methods: Patients with LS-SCLC treated with concurrent chemo-radiotherapy from May 2008 to December 2020 in our hospital were retrospectively analyzed. The prescribed radiation dose was 60Gy administrated with conventional RT in 30 fractions within 6 weeks. The prognostic role of cycle number of chemotherapy administrated concurrently with RT were analyzed. All patients were followed up at one month after the treatment, then once every three months until two years after the treatment, and every six months thereafter. Propensity score matching (PSM) was performed to reduce confounding factors. The primary endpoint was overall survival (OS). Survival analysis was performed with Kaplan-Meier and multivariate analysis was performed with Cox regression model. Results: Among the 370 patients who received radical radiotherapy, 206 patients received concurrent chemo-radiotherapy and were included for the analysis. Multivariate analysis showed that stage and PCI were independent prognostic factors for OS. The median OS in patients who received one cycle and two cycles of chemotherapy concurrently with RT were 32.9 months and 31.6 months, respectively (P = 0.241). And the median PFS were 20.6 months and 18.4 months, respectively (P = 0.764). After PSM, no statistical differences in OS and PFS were observed between patients who received one cycle and those who received two cycles of concurrent chemotherapy. Conclusion: Two cycles of concurrent chemotherapy during RT were not necessarily superior compared to one cycle in LS-SCLC. The optimal cycle number of concurrent chemotherapy during RT needs to be further studied. Keywords: Limited-stage small cell lung cancer, concurrent chemoradiotherapy, prognosis Abbreviations: LS-SCLC = limited-stage small cell lung cancer; OS = Overall survival; PFS = Progression-free survival; PSM = Propensity score matching; PCI = Prophylactic Cranial Irradiation; RT = Radiotherapy